La compañía Finlandesa Outokumpu desarrollo y prensencia editorial en el sector minero-metalúrgico mexicano - Álvaro Sánchez Crispín (Investigaciones Geográficas, 1995)
This paper examines the territorial impact of the presence of the Finnish mining company, Outokumpu Oy. in the mining sector of Mexico. The papers describes the expansion of the company, beyond the limits of Finland, the development of mining technology achieved by Outokumpu Oy and how this derives into the selling of specific mining techniques and machinery to different countries, Mexico included. The final part of the paper deals with the issue of the territorial presence of Outokumpu Oy in the Mexican mines.